1967
DOI: 10.1104/pp.42.4.479
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Changes in After-Ripening Seed of Prunus cerasus

Abstract: SiuJtil(ry. Metabolic changes were sttudied in emllbryvonic axes and cotyledons isolated fromii after-ripeniing seeds of Pru-nus ccrasus. Dutring the sevenith week of after-ripening, a striking increase in the respirationi rate at 250 of embryonic axes occuirre(l along with a sharp chanige from the dormant to non-dormant state of the see(l. On the basis of C-6/C-1 ratio determinatioiis this chanige may be related to an increased activity of the pentose phosphate cvcle. Ba'4C03, plated on microporous porcelain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1968
1968
2006
2006

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…It is not clear how chilling brings about the loss in embryo dormancy, but it may involve mobilization of food reserves such as carbohydrates (La Croix and Jaswal 1967) and lipids (Ross 1984). Our results indicate that the minimum period for stratification is 6 wk when some seed exhibited a physiological response to the treatment.…”
Section: Discussionmentioning
confidence: 74%
“…It is not clear how chilling brings about the loss in embryo dormancy, but it may involve mobilization of food reserves such as carbohydrates (La Croix and Jaswal 1967) and lipids (Ross 1984). Our results indicate that the minimum period for stratification is 6 wk when some seed exhibited a physiological response to the treatment.…”
Section: Discussionmentioning
confidence: 74%
“…This hypothesis implies that the significance of the increased rate of oxygen uptake which occurs during the after-ripening of some seeds may be associated with the activity of new oxidative pathways rather than simply the increased activity of a particular pathway. LaCroix and Jaswal (9) reported that germination of cherry seeds appeared to be correlated with an increase in the activity of the pentose phosphate pathway in the embryonic axes. Additional support for the hypothesis was provided by the demonstration that qualitative changes in oxidative metabolism occurred in the period of constant oxygen consumption during after-ripening of wild oat caryopses (16 A decrease in the activity of ATP-generating systems by a high energy charge alone would result in the restricted production of biosynthetic intermediates at a time when the energy supply was plentiful.…”
Section: Discussionmentioning
confidence: 99%
“…Direct evidence of an increase in activity of the OPP pathway associated with loss of donnancy has only been reported in two other species besides barley, i.e. Prunus cerasus (~a Croix and Jarwal, 1967) and Avenafatua (Simmonds and Simpson, 1971). …”
Section: Discussionmentioning
confidence: 96%